SYNERGETIC PROGRESS OF INVESTMENT PROCEDURES - Abitovna, Khashimova Naima; Khilola, Bakhodirova; Azimjon, Aliyev (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the problems of investment potential and ways of its activation and determines the share of state regulatory influences with the provision of freedom and initiative for self-regulatory economic entities. The role of foreign investment in the growth of investment potential is determined. The synergetic principle of the mechanism of formation, regulation and self-regulation of investment activity, which fits into the basic laws of the theory of synergetics, is substantiated.